Home at last : the re-entry adaptation of returned South African exiles - Majodina, Zonke (Department of Psychology, 2023)
Although promoted as the most durable solution to problems caused by forced migration, voluntary repatriation has proved to be a most difficult solution owing to the numerous psychosocial, economic, legal and political problems associated with it. This thesis is a report of an investigation into the complex set of personal and social factors that determine the adaptation of returning South African exiles. In Chapter 1, an account is given in broad outline of the present state of knowledge regarding the issue of repatriation as well as psychological explanations of cultural adaptation. Re-entry into the home culture after a period of forced absence is conceptualized as one aspect of cultural adaptation. Chapter 2 looks at the historical, international context of voluntary repatriation, focusing on the evolution of international refugee policy. Against the background of the intractable problems that elude the possibility of a permanent solution, a few repatriations to African countries are reviewed. In Chapter 3, psychological studies of the refugee/exile expenence are reviewed. Early psychological research examined the refugee experience from a medical perspective. This has led to a conceptualization of forced migration as a stress provoking process, with refugees reported to have a higher incidence of psychiatric disturbance than native born populations in host countries. Not surprisingly, the term post-traumatic stress disorder has become a frequently used term in relation to refugee adaptation. With the advent of more sophisticated multivariate methods of analysis, multidimensional models of adaptation have been developed. These consider adaptation to be a product of multiple interacting factors operating at various levels, thus taking into account the complexity of the refugee situation. Finally, acculturation models, notably Berry's acculturation framework focus on how individuals who have developed in one cultural context manage to adapt to new contexts that result from migration. The acculturation approach highlights the complex interactions and patterns of continuity and change people go through in new environments. Chapter 4 reviews research which shows that returning home can be as or more disturbing than living in exile. The chapter begins by conceptualizing re-entry as part of the larger issue of cultural adaptation. Studies of returning short-term migrants are reviewed and the centrality of re-entry difficulties noted. There are comparatively fewer psychological studies of repatriation of refugees/exiles from countries of asylum. The majority of studies in this domain are carried out from diverse disciplinary backgrounds but consistently report the prominence of economic difficulties of return. In Chapter 5, the socio-economic and political context of return for South African exiles is examined. The chapter begins by highlighting the major milestones in the history of resistance to apartheid and traces events leading to the advent of a post-apartheid South Africa. Concerning the repatriation exercise, it discusses the role played by the major stakeholders, namely, the South African government, NCCR and the UNHCR. This is followed by a consideration of returning to a situation of violence and uncertainty. Reports of dissatisfaction with conditions on return were common. Problems of employment, schooling, housing and feeling unwelcome often led to deep feelings of despair among returnees. Chapter 6 gives the rationale as well as an account of the methodology adopted for the study. Berry's acculturation framework, complemented by Nicholson's transition cycle theory forms the theoretical basis on which the study is based. The various components of the study are described under the methodology section and methodological difficulties of conducting a study of this nature are highlighted. With the collection of data completed, Chapter 7 gives an account of the various preliminary steps taken to prepare the data for statistical analysis. This included checking the data for completeness, accuracy and uniformity as well as examining the properties of the scales used in the questionnaire. Chapter 8 presents the results. The descriptive section of the results indicates that the majority of respondents adapted relatively well to exile life. They had high expectations of what would happen when they returned home. These high expectations were however mostly unfulfilled upon return. Furthermore, respondents reported that they experienced re-entry difficulties at various levels of severity. In the face of such great disappointment and difficulties in adapting back, the family was reported to be the main source of social support. In terms of how close they felt to either home or exile, most returnees indicated a closer affinity with home. More detailed analysis of the data indicated that re-entry difficulties had the most important influence on adaptation outcome. Chapter 9 discusses and elaborates on these results. The return of the sample of exiles under study was overshadowed by the severe difficulties they faced as they negotiated their way back into a now alien environment. This finding verifies empirically the commonplace fact that following the experience of being forcibly uprooted, people face tremendous challenges of adapting to a country they were forced to flee. The implications of this finding are that much as repatriation has been promoted as a durable solution to the refugee 'problem', the serious material, social and emotional difficulties accompanying return render it a most problematic solution. This reinforces the argument that the most important criterion to consider in any repatriation is neither the numbers nor the orderly physical movement of people across borders but how well they adapt to conditions of living in the new place called 'home'. It also supports the contention that returning exiles are not returning to the idealized home but to a country of origin. Thus the central thesis of my study is simple enough - repatriation as it is presently conceived is regarded as a solution to the refugee problem, an end point, and not as a completely new beginning on new terrain. Yet this simple fact does not seem to have been acknowledged thus far. The many repatriations that have taken place indicate that far from being an end point, repatriation is in fact a beginning. It is my modest hope that my study will help contribute to a better understanding of the repatriation process and to approach it as the problem that it is instead of assuming that it is the solution to problems of forced migration.